Physics of Everyday Phenomena - W.Thomas Griffith (McGraw -Hill, 2003)
The satisfaction of understanding how rainbows are formed ,how ice skatars spin ,or why ocean tides roll in and out-phenomena that we haveall seen or experiinced - is one of the best motivators available for building sci-entific literacy.this book attempts to made that sense of saticfaction accessible to non-science majors .Intended for use in a one-semester or two-quarter course in con-ceptual physict ,this book is wrtten in a narrative style ,frequently using questions desingne to draw the reader into a dialogue about the ideas of physics .this inclu-sive style allows the book to be used by anyone inter-ested in exploring the nature of physics and explanations of everyday physical phenomen.